EXPLORING THE DRIVERS OF EMPLOYEE PERFORMANCE: THE ROLE OF OCB, WORK-LIFE BALANCE, AND JOB SATISFACTION IN AN INDONESIAN MANUFACTURING FIRM - Gunawan, Yanthi Meitry; Kholifah, Siti (Universitas Muhammadiyah Tangerang, 2025)
This study examines the influence of organizational citizenship behavior, work-life balance, and job satisfaction on employee performance at PT. HTP Metalworks, a manufacturing company facing challenges in maintaining productivity amid increasing operational demands. The research addresses a critical gap in the context of Indonesian SMEs, where employee well-being and discretionary efforts are often overlooked. Using a quantitative approach with a saturated sample of 80 employees, primary data were collected through questionnaires and analyzed using regression analysis. Results indicate that all three variables significantly and positively influence employee performance, both individually and collectively, with a combined explanatory power of 58.4%. This highlights the importance of fostering supportive work environments and positive employee attitudes. The study contributes theoretically by integrating social exchange and job demand-resource theories in a developing economy context, and practically by offering actionable insights for HR management in similar industrial settings.